Strategi Dakwah melalui Short Form Video TikTok pada Akun @hafazzz dalam Meningkatkan Pengamalan Puasa GEN Z - Sri Indah Wati Harahap; Muhammad Husni Ritonga (CV Global Research Publication, 2026)
The study is grounded in the growing dominance of TikTok as an information consumption platform among Gen Z, alongside the declining consistency of fasting observance attributed to digital distractions and modern lifestyle transformations. The study aims to analyze the da'wah strategy implemented through the TikTok account @bghafazzz by utilizing short-form video content. A qualitative approach was employed, with data collected through observation and documentation of content uploaded during February 2026. The data were analyzed through the stages of data reduction, data display, and conclusion drawing. The findings reveal that the @bghafazzz account applies three pillars of da'wah strategy: sentimental (emotional packaging through music, visuals, and reflective narratives), rational (concise fiqh explanations and practical question-and-answer sessions), and interactive (video replies, fasting challenges, and an active comment section). These strategies are delivered through a casual communication style, first-person perspective format, consistent visual identity, and a peer-to-peer approach that builds emotional connection and increases Generation Z's motivation to observe fasting consistently. Nevertheless, the inherent time constraints of the short-form format demand a careful balance between creative packaging and substantive accuracy to prevent oversimplification of religious meaning. Theoretically, this study contributes the TikTok Short-Form Transformational Da'wah Theory (DTSTT), which identifies three interrelated psycho-spiritual mechanisms underlying religious transformation in Generation Z: cognitive absorption, emotional resonance, and behavioral modeling.